Calliphoridae, fanniidae e muscidae (diptera) associados à material orgânico animal em Feira de Santana, Bahia - Monteiro, Thayana Teles d’Alencar (2012)
Taxonomic survey and seasonality of Calliphoridae, Muscidae and Fanniidae (Diptera) in Feira de Santana, Bahia. Taxonomic studies in necrofhagous Diptera is relevant because its importance in forensic, health and medical porpouses, whereas its feed in decaying organic matter as protein source, at least in one stage of their lives. Synantropic Diptera, such some species of Calliphoridae, Muscidae and Fannidae had not been studied in Feira de Santana, BA. The aim of this study was collect necrophagous Diptera belonging to the families cited above in Feira de Santana. Fifteen baited traps (24 hours exposure) were placed in three areas of the town, once a month, performing a total of 12 samples. A total of 4.818 specimens were collected belonging to 20 species: Calliphoridae (6 species), Fannidae (3 species) and Muscidae (11 species). Fall was the season with higher abundance, in opposite to summer, with lower abundance. Thirteen (65%) out of the twenty species collected were cited in literature as of forensic importance.